Quantum Abelian Yang-Mills Theory on Riemannian Manifolds with Boundary - Díaz-Marín, H.G.; Oeckl, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We quantize abelian Yang-Mills theory on Riemannian manifolds with boundaries in any dimension. The quantization proceeds in two steps. First, the classical theory is encoded into an axiomatic form describing solution spaces associated with manifolds. Second, the quantum theory is constructed from the classical axiomatic data in a functorial manner. The target is general boundary quantum field theory, a TQFT-type axiomatic formulation of quantum field theory.